Relationship Between Knowledge and Behaviour of Self-Medication in Cough Towards One Community in East Java - Netta, Shella Naradewi; Hajma, lilla Prapdhani Agni (Universitas Muhammadiyah Surakarta, 2024)
Coughing is often considered a minor illness, but in reality it disrupts daily activities. In dealing with coughs, treatment can be done independently or known as self-medication. In Indonesia, the practice of self-medication tends to increase. However, improvement in self-medication practices is often not aligned with adequate knowledge. This research aims to determine the profile of self-medication in society, the level of self-medication knowledge, the level of self-medication behaviour, and analyze the relationship between knowledge and behaviour. Questionnaires that have been tested for validity and reliability on 30 respondents are used as instruments. The data collection method was carried out cross-sectionally using a purposive sampling technique in September-November 2023. Respondents in this study were community in one of the regions in East Java with the inclusion criteria. The total respondents in this study were 363 respondents. Univariate analysis was carried out on self-medication profile, level of knowledge, and level of behaviour. The relationship between level of knowledge and behaviour was analyzed using the Spearman Rank method. In this study, the average community knowledge score was 76.86% with a good level of knowledge (54.3%). In the behavioral variable, the average value is 77.39% with the good behaviour level category (59%). There is a relationship between the level of knowledge and cough self-medication behaviour in the community as evidenced by a sig. (2-tailed) 0.000. A positive correlation coefficient of 0.49 was obtained thus indicating that the strength of the relationship between knowledge level and behavior is moderate.